2021
DOI: 10.1371/journal.pone.0254641
|View full text |Cite
|
Sign up to set email alerts
|

Delayed repolarization and ventricular tachycardia in patients with heart failure and preserved ejection fraction

Abstract: Sudden death is the most common mode of mortality in patients with heart failure and preserved ejection fraction (HFpEF). Ventricular arrhythmias (VA) have been suspected as the etiology but the supporting evidence in patients with HFpEF is scarce. We sought to investigate VA prevalence, and to determine if VA are associated with prolonged repolarization, in patients with HFpEF. In a retrospective case-control study design, Cedars-Sinai patients who underwent prolonged ambulatory electrocardiographic monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“… 37) Covariate-adjusted logistic regression showed that HFpEF was associated with an increased risk of NSVT. 37) Another important prospective observational study was done (VIP-HF study) in the Netherlands for patients with HFpEF using an implantable loop recorder. 38) Eighteen percent of HFpEF patients were shown to have NSVT during the median follow-up of 657 days.…”
Section: Ventricular Arrhythmias In Heart Failure With Preserved Ejec...mentioning
confidence: 99%
See 4 more Smart Citations
“… 37) Covariate-adjusted logistic regression showed that HFpEF was associated with an increased risk of NSVT. 37) Another important prospective observational study was done (VIP-HF study) in the Netherlands for patients with HFpEF using an implantable loop recorder. 38) Eighteen percent of HFpEF patients were shown to have NSVT during the median follow-up of 657 days.…”
Section: Ventricular Arrhythmias In Heart Failure With Preserved Ejec...mentioning
confidence: 99%
“… 36) Most importantly, NSVT was associated with a 3.4-fold increased risk of death in HFpEF patients. 36) A similar retrospective medical record review was done by Cho et al 37) for HFpEF patients who underwent ambulatory Zio patch monitoring. Similarly, NSVT was found in 37% of HFpEF patients, as compared to 16% occurrence in patients without HFpEF.…”
Section: Ventricular Arrhythmias In Heart Failure With Preserved Ejec...mentioning
confidence: 99%
See 3 more Smart Citations